2023
DOI: 10.3390/jcm12051834
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Biopsy in Pregnant Women with Glomerular Diseases: Focus on Lupus Nephritis

Abstract: Despite significant improvements of renal and obstetrical management, pregnancies in women with glomerular diseases and with lupus nephritis continue to be associated with increased complications both for the mother and the fetus as compared to those of pregnancies in healthy women. To reduce the risk of these complications, planning pregnancy in a phase of stable remission of the underlining disease is necessary. A kidney biopsy is an important event in any phase of pregnancy. A kidney biopsy can be of help d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 77 publications
0
1
0
Order By: Relevance
“…Imaging tests, including renal ultrasound or CT, may also be necessary to diagnose cortical necrosis or obstructive uropathy [8]. Occasionally, a renal biopsy may be necessary to confirm the diagnosis and to help with prognosis if evidence of impairment persists [9].…”
Section: Discussionmentioning
confidence: 99%
“…Imaging tests, including renal ultrasound or CT, may also be necessary to diagnose cortical necrosis or obstructive uropathy [8]. Occasionally, a renal biopsy may be necessary to confirm the diagnosis and to help with prognosis if evidence of impairment persists [9].…”
Section: Discussionmentioning
confidence: 99%
“…Biopsy is usually considered in pregnancy when progressive kidney function impairment and/or severe proteinuria could interfere with pregnancy outcomes and when establishing a diagnosis is needed to determine treatment. 6 The procedure should be considered possibly before 25 weeks of gestation age to reduce the risk of bleeding complications after biopsy, as alluded by Pontichelli et al 27 in a recent review on kidney biopsy in pregnant women with LN. 27 A systematic narrative review of nearly 200 kidney biopsies performed during pregnancy showed that the procedure is associated with a relatively small (2%) but increased risk of bleeding complication particularly around 25 weeks of gestation.…”
Section: Role and Timing Of Kidney Biopsy During Pregnancy In Patient...mentioning
confidence: 99%